A study on factors infuence the usage of recyclable and biodegradable products in Malaysian Households / Nurul Habibah Hassan and Raihan Ismadi - Hassan, Nurul Habibah; Ismadi, Raihan (2022)
The purpose of the study was to examined the relationship of green knowledge, price and environmental awareness on the usage of recyclable and biodegradable products among Malaysian households. The study was conducted from October 2021 to August 2022. In this study, data collection obtained through questionnaire survey. The result of the study revealed two major findings. First, there are a significant relationship between green knowledge, price and environmental awareness on the usage of recyclable and biodegradable products. Second, majority of the respondents were agreed that environmental awareness is the strongest predictor that influences the usage of recyclable and biodegradable products. As a result, this studies uniquely positioned to make both theoretical and empirical contributions to the multi-domain literature including sustainability and environmental management.